Effect of Stimulant Medication on Growth - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Twenty-nine studies of growth in height of children (22) and late adolescents (7) with attention deficit hyperactivity disorder (ADHD) treated with stimulant medication were reviewed at the University of Sydney, Australia.